PWE-276 Validation of fibroscan as a screening tool for cystic fibrosis associated liver disease in an adult population. (28th May 2012) - Swann, R E; Mustafa, Z; Ross, E; Priest, M
Abstract : Introduction: Cystic fibrosis (CF) associated liver disease affects up to 41% of CF sufferers and may progress to cirrhosis with associated complications. 1 Diagnosis is frequently made without biopsy. A recent study evaluated the use of fibroscan in diagnosis of CF associated liver disease (CFLD) in the paediatric context, however there are now many adult patients with cystic fibrosis, therefore we aimed to validate the ability of fibroscan to assess liver disease severity in an adult CF population. 2 3 Methods: We recruited a cohort of adult CF patients diagnosed in the paediatric setting with CFLD and a control cohort with CF but no clinical or biochemical evidence of liver disease. All patients were assessed for clinical, radiological or biochemical evidence of liver disease by the authors and underwent a fibroscan. Fibroscan results were correlated with clinical evidence of liver disease. Results: We recruited 20 patients, 11 with normal liver biochemistry, no clinical evidence of liver disease and normal liver ultrasound scans (NLF group) and nine with a historical diagnosis of CF associated liver disease. Six of these had abnormal liver function tests but no clinical, radiological or endoscopic evidence of cirrhosis (Intermediate—I) and three patients had significant liver disease with evidence of portal hypertension at endoscopy (SLD). Correlation of fibroscan result with clinical group was performed. The difference between the SLD group and the NLF group was significant (p=0.002) by the Mann–Witney U test. A ROC analysis suggested a cut-off of 11.2 kPa for cirrhotic CFLD as having the highest accuracy. However this requires further validation with a larger cohort of patients. There was strong correlataion of fibroscan reading with APRI score with an R 2 value of 0.757. Conclusion: Fibroscan correlates well with clinical assessment of CFLD severity in our cohort of adult CF patients and may help clarify diagnosis. We continue to recruit patients and hope to determine appropriate cut-off values for further investigation. Competing interests: None declared. Reference: 1. Lamireau T, Monnereau S, Martin S, et al. J Hepatol 2004;41 :920–5. 2. Witters P, De Boeck K, Dupont L, et al. J Cyst Fibros 2009;8 :392–9. 3. Leonard A, Menten R, Clapuyt P, et al. J Cyst Fibros 2008;7 (Suppl 2):S82.